KARAKTER MASYARAKAT ISLAM MELAYU PALEMBANG - Alhamdu Alwi (Psikoislamedia : Jurnal Psikologi, 2018)
The purpose of this study is looking for character of Islamic Melayu Palembang society, and what the factors influenced transformation of character in Islamic Melayu Palembang society. Mix methode approaches (qualitative and quantitative descriptive reseach) used for answering problem formulation, with 7 peoples as qualitatif subject, and 200 respondens as quantitative subject. The result of this study described about 5 characters of Islamic Melayu Palembang society, there are humorist (57.5%), respectful (20.5%), well mannered (8.5%), diligent (8%), and lazy (5.5%). This study also found that transformation of character in Islamic Melayu Palembang society happened, specifically for well mannered character. The transformation of character occured because of inhabitant growth, higher necessary of lives, transmigration and urbanitation, and effect of technolgies, information, and globalitation era which uncontrolled by family and Islamic Melayu Palembang society. Keywords: Character, Melayu, Palembang, Culture.